A molecular phylogeny of the vataireoid legumes underscores floral evolvability that is general to many early‐branching papilionoid lineages1. Issue 2 (1st February 2013) - Cardoso, Domingos; Paganucci de Queiroz, Luciano; Cavalcante de Lima, Haroldo; Suganuma, Elisa; van den Berg, Cássio; Lavin, Matt
Abstract : Premise of study: Flowering traits can sometimes be overemphasized in taxonomic classifications. The fused and completely differentiated papilionate floral organs in the neotropical legume trees Vatairea and Vataireopsis were traditionally used in part to ascribe these genera to the tribe Dalbergieae. In contrast, the free and mostly undifferentiated floral parts of Luetzelburgia and Sweetia fit the circumscription of the "primitive" Sophoreae. Such divergent floral morphologies thought to divide deep phylogenetic lineages indeed may be prone to episodic transformation among close papilionoid relatives. Methods: We sampled 26 of 27 known species of Luetzelburgia, Sweetia, Vatairea, and Vataireopsis in parsimony and Bayesian phylogenetic analyses of nuclear ribosomal ITS/5.8S and six plastid ( matK, 3′ ‐trnK, psbA‐trnH, trnL intron, rps16 intron, and trnD‐T ) DNA sequence loci. Key results: The analyses of individual and combined data sets strongly resolved the monophyly of each of Luetzelburgia, Sweetia, Vatairea, and Vataireopsis . Vataireopsis was resolved as sister to the rest and the morphologically divergent Luetzelburgia and Vatairea were strongly resolved as sister clades. Floral morphology was generally not a good predictor of phylogenetic relatedness. Conclusions: Luetzelburgia, Sweetia, Vatairea, and Vataireopsis are unequivocally resolved as the "vataireoid" clade. Fruit and vegetative traits are found to be more phylogenetically conserved than many floral traits. This explains why the identity of the vataireoids has been overlooked or confused. The evolvability of floral traits may also be a general condition among many of the early‐branching papilionoid lineages.